Uncovering the hidden costs by evaluating ecological costs - Ignatius Novianto Hariwibowo (Jurnal Ekonomi dan Bisnis, 2021)
This study aims to calculate the environmental costs of a sugar cane producer. Worsening environmental problems have required the company to implement environmental management practices. Nevertheless, the results of these environmental management practices need to be evaluated by comparing its ecological costs (eco-costs) as the external costs with costs allocated by the company to manage the environment. Accordingly, this study employs the case study at a cane sugar producing company located in Yogyakarta Specific Region Province. Furthermore, we combine two environmental cost calculation methods, namely the Environmental Management Accounting (EMA) and Life Cycle Assessment (LCA) methods. The EMA approach seeks to identify prevention and compensation costs. Meanwhile, the LCA approach is used to calculate eco-costs. We convert the eco-cost values based on the values from the table of ecological cost values at www.ecocostsvalue.com. The results of this study show that the company incur environmental impact costs much greater than its prevention and compensation costs. These findings indicate that the company has not incorporated hidden environmental costs in its environmental management.